Hepatoprotective Activities of Ethanolic Roots Extract of Ageratum Conyzoides on Alloxan-Induced Hepatic Damage in Diabetic Wistar Rats - Ojewale, A.O.; Akpan, H.B.; Faduyile, F.A.; Shallie, P.D.; Akande, A.A.; Adefule, A.K. (Journal of Morphological Sciences, 2019)
Introduction The aim of the present study was to evaluate the hepatoprotective activities of the ethanolic roots extract of Ageratum conyzoides (AC) in alloxan-induced hepatic damage in diabetic rats.Materials and Methods Diabetes was induced in Wistar rats by the administration of alloxan (150 mg/kg, intraperitoneal). The ethanolic roots extract of AC, at doses of 250 and 500 mg/kg of body weight, was administered to diabetes-induced rats at a single dose per day for a period of 28 days.Results The effect of the ethanolic roots extract of AC on blood glucose, alanine aminotransferase (ALT), aspartate aminotransferase (AST), and hepatic oxidative stress markers was measured in the diabetic rats. The ethanolic roots extract of AC exhibited significant reduction of blood glucose (p < 0.05) at the dose of 500 mg/kg when compared with the standard drug glibenclamide (600 µg/kg). The alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels increased significantly (p < 0.05) in the diabetic group without treatment when compared with the control group. In addition, the levels of oxidative stress markers, such as superoxide dismutase (SOD), catalase (CT), glutathione peroxidase (GPx), and glutathione (GSH), were significantly decreased in the diabetic rats compared with the normal rats, while the lipid peroxidation significantly increased in the diabetic group without treatment compared with the control (normal) group. The results demonstrated that the morphological, functional and oxidative stress changes in the liver caused by the ingestion of alloxan were attenuated in diabetic rats treated with the ethanolic roots extract of AC.Conclusion We concluded that the ethanolic roots extract of AC possesses significant antidiabetic, antioxidant and hepatoprotective effects on alloxan-induced diabetic rats.
Keywords: hepatoprotective activity; antioxidants; alloxan; rats; ageratum conyzoides